1978
DOI: 10.1037/0021-843x.87.4.459
|View full text |Cite
|
Sign up to set email alerts
|

A methodological study of the effect of experimentally induced demand characteristics in research on nocturnal dreams.

Abstract: This experiment tested the hypothesis that demand characteristics may influence dream content. Laboratory and home dreams were collected from 12 subjects allocated to two matched groups. The independent variable, a simple form, was administered to each group and requested that the subjects in the respective groups pay special attention to either the outdoor-nature or urban settings of their nocturnal dreams. The subjects did not consciously construe these forms as representing an attempt to influence their dre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In the present study, the participants were recruited for a sleep and dream study without special reference to music in dreams. Second, asking participants directly about music in their dreams every morning with probing questions can bias the results -similar to a previous study about outdoor and urban settings (Stern, Saayman, & Touyz, 1978). In that study the participants who were explicitly asked about one topic every morning reported more dreams including this topic over the course of the study.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, the participants were recruited for a sleep and dream study without special reference to music in dreams. Second, asking participants directly about music in their dreams every morning with probing questions can bias the results -similar to a previous study about outdoor and urban settings (Stern, Saayman, & Touyz, 1978). In that study the participants who were explicitly asked about one topic every morning reported more dreams including this topic over the course of the study.…”
Section: Discussionmentioning
confidence: 66%
“…Previous research (cf. Stern, Saayman, & Touyz, 1978) has shown that instructions can bias dream content in a sense that contents like urban settings are more frequent if the participants were specifically asked about it. Second, Uga et al (2006) did not reported means of how much time the two groups spend with listening to music during the day.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that urging subjects to pay attention to either the rural or the urban settings that occurred in their dreams influences the dream content. Specifically, people who were instructed to pay attention to an urban setting were more likely to report urban-setting dreams (Stern, Saayman, & Touyz, 1978). In another study, subjects were urged to pay attention to either times when they were with many people or times when they were alone.…”
Section: Does Waking Materials Influence Dream Content?mentioning
confidence: 98%